Risk assessment in air navigation system methods of the theory of fuzzy sets - Харченко, В.П.; Чинченко, Ю.В.; Райчев, С.Г.; Луппо, О.Є. (Proceedings of National Aviation University (archive), 2008)
The method of risk analysis in the aeronautical system with application of fuzzy logic theory is proposed. Results of experimental researches about quantitative-qualitative estimation of risks, which are typical for the air traffic system are analyzed.